Molecular footprints of the Holocene retreat of dwarf birch in Britain. Issue 11 (16th May 2014) - Wang, Nian; Borrell, James S.; Bodles, William J. A.; Kuttapitiya, Anasuya; Nichols, Richard A.; Buggs, Richard J. A.
Abstract Past reproductive interactions among incompletely isolated species may leave behind a trail of introgressed alleles, shedding light on historical range movements. Betula pubescens is a widespread native tetraploid tree species in Britain, occupying habitats intermediate to those of its native diploid relatives, B. pendula and B. nana. Genotyping 1134 trees from the three species at 12 microsatellite loci, we found evidence of introgression from both diploid species into B. pubescens, despite the ploidy difference. Surprisingly, introgression from B. nana, a dwarf species whose present range is highly restricted in northern, high‐altitude peat bogs, was greater than introgression from B. pendula, which is morphologically similar to B. pubescens and has a substantially overlapping range. A cline of introgression from B. nana was found extending into B. pubescens populations far to the south of the current B. nana range. We suggest that this genetic pattern is a footprint of a historical decline and/or northwards shift in the range of B. nana populations due to climate warming in the Holocene. This is consistent with pollen records that show a broader, more southerly distribution of B. nana in the past. Ecological niche modelling predicts that B. nana is adapted to a larger range than it currently occupies, suggesting additional factors such as grazing and hybridization may have exacerbated its decline. We found very little introgression between B. nana and B. pendula, despite both being diploid, perhaps because their distributions in the past have rarely overlapped. Future conservation of B. nana may partly depend on minimization of hybridization with B. pubescens, and avoidance of planting B. pendula near B. nana populations.